Adjustment of Biomass Yield to a Dry Matter Basis in Switchgrass Breeding: A Necessity or a Nuisance?. Issue 4 (17th May 2018) - Casler, M. D.
Abstract : Increases in biomass yield of switchgrass ( Panicum virgatum L.) have been achieved, but the rate of gain has been slow and would benefit from improved efficiency of selection methods. Dry matter (DM) determinations at the time of harvest are a traditional method to adjust fresh matter yield (FMY) to a DM basis. The purpose of this study was to determine if DM determinations in switchgrass yield evaluations are necessary or unnecessary. Data from 219 trial‐years of 11 published experiments were used to evaluate the value of DM adjustment. Heritability for FMY and dry biomass yield (DBY) were similar, and the genetic correlation between these two traits was >0.8 for 96.7% of the trial‐years. The direct effect of FMY on DBY was three to four times greater than the direct effect of DM concentration. Because DM determination requires a larger field crew at the time of harvest, the use of FMY as a selection criterion requires significantly less labor than DBY at harvest time. Tripling the number of families evaluated and eliminating the DM step would increase the expected genetic gain for DBY by 17%. However, decreasing the number of replicates per family while eliminating the DM step would undermine the gains in efficiency due to reduced heritability for FMY. Although the risk of using FMY is low, achieving this increase in efficiency requires a serious commitment to evaluating a very large number of replicated families in each generation, an effort that may be beyond the ability and scope of most breeding programs.